The Psychiatric Interview: A Self-Directed Learning Module - Hendry Ton; Glen Xiong; Lina Méndez; Donald Hilty; Lawrence Price; Robert Brescia; David Patron (Association of American Medical Colleges, 2013)
Abstract Introduction Gathering clinical information about the patient in a therapeutic manner is an important interviewing goal, particularly for the psychiatric interview. Psychiatry clerkship students may use this self-learning module (SLM) to prepare for their first supervised psychiatric interview. Alternatively, this module can help first- and second-year students in a behavioral medicine or psychopathology course prepare for a standardized patient interview. Methods This module presents video clips of a psychiatrist conducting a psychiatric interview of a patient with depressive symptoms. Samples of the key components of the interviews, such as the chief complaint, history of present illness, past treatment history, social and developmental history, cognitive exam, and risk assessment are taught using combinations of video clips, interactive diagrams, and selfassessment quizzes. Additionally, basic interview techniques are discussed and illustrated during the interview. Results This SLM has been implemented within the psychiatry clerkship at the University of California Davis, School of Medicine and piloted in the psychiatry clerkships at both Georgia Health Science University and the University of Florida School Of Medicine. This module was piloted by four students and two faculty members. One of the two faculty reported that the SLM could be adapted for first-, second-, and third-year medical students, as well as to behavioral health students. Three out of four students somewhat agreed or strongly agreed that the module: (a) increased their comfort level with performing the psychiatric interview, (b) increased their comfort level with interacting with mentally ill patients, and (c) increased their comfort level of assessing risk of harm. All four students somewhat agreed or strongly agreed that the module increased their comfort level both with applying psychiatric interview techniques in patient interactions and eliciting a symptom history from patients. This SLM was also presented at the 2011 Association of Directors of Medical Student Education in Psychiatry (ADMSEP) Poster Session where we received extensive feedback and won the ADMSEP "2011 Outstanding Education Poster Award." Discussion Gathering clinical information about the patient in a therapeutic manner is an important interviewing goal, particularly for the psychiatric interview. This resource successfully teaches learners the components of the psychiatric interview.